Improving personal hygiene practices through health cadre training: a case study in a boarding school - Fajrul Falah Farhany; Ichwan Ichwan; Fitriana Aulia Sabila Eka Putri; Miftahurrahmah El Hayatli; Dita Stiana; Hanggoro Tri Rinonce; Happy Indah Kusumawati; Shinta Trilaksmi Dewi (Universitas Gadjah Mada, 2024)
Purpose: To assess changes in SHCs’ scabies-related knowledge after a brief training and to explore feasibility, acceptability, and implementation challenges. Methods: Explanatory-sequential mixed-methods study at a Yogyakarta Islamic boarding school. The quantitative strand employed a one-group pretest–posttest design with a 10-item knowledge score (0–10), and a paired t-test was used to analyze the data. The qualitative strand comprised semi-structured interviews with SHCs, and the data were analyzed thematically. Results: Thirty-five SHCs completed both assessments (51.4% female). Mean knowledge increased from 6.26 ± 1.46 to 7.94 ± 1.26 with Δ = 1.69 ± 2.21, t(34) = 4.52, p < 0.001, and Cohen’s dz ≈ 0.76. The proportion with good knowledge rose from 20.0% to 71.4%. The largest gains involved bathing with soap, changing clothes after sweating or dust exposure, and not sharing personal items, whereas declines were observed in mattress-airing frequency and a stigma item. Interviews indicated acceptability and feasibility, and highlighted irregular coordination and the absence of a formal SHC structure. Item-level interpretations are exploratory. Conclusions: A brief training for SHCs was associated with a statistically significant within-group increase in scabies-related knowledge and appeared feasible in dormitory settings. Scale-up should pair concise training with a formal SHC structure, scheduled coordination, orientation-time sessions, and simple visual prompts. Future research should evaluate retention, observable behaviors, and incidence with a comparison or cluster design to determine the preventive impact.